Rituales corporativos y el compromiso laboral del colaborador en un banco peruano - Chavez-Luna, Luis (2020)
This study explore the existence of a possible relationship between participation in corporate rituals and the employee commitment to the company. This case study examines the “Banco de Crédito del Perú (BCP)”. Questionnaires where designed using Microsoft Forms. A convenience sampling of 379 employees participated in this study. As revealed in the findings, there is no relationship between the employee commitment and the number of rituals in which he participates. Millennial collaborators mostly participate in only 1 to 2 rituals within the company with 27% and 31% respectively; being the Halloween contest the ritual that has the highest ratio of millennials who do not participate.